Co-doped Fe-Co-N-C catalyst for advanced oxidation treatment of wastewater and preparation method of Co-doped Fe-Co-N-C catalyst
The Co-doped Fe-Co-N@C catalyst addresses the issue of symmetrical Fe-N4 structure adsorption by creating an asymmetric coordination with enhanced polarization and electron donation, achieving superior PMS activation and pollutant removal efficiency.
Patent Information
- Application Number
- CN202411286759.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-13
AI Technical Summary
Symmetrical Fe-N4 structures in traditional Fe-N catalysts cause strong intermediate adsorption, limiting catalytic activity due to shielding of active sites, and resulting in poor PMS activation performance.
A Co-doped Fe-Co-N@C catalyst is prepared through a three-step method involving metal-organic framework material formation and post-coordination, creating an asymmetric coordination structure with enhanced polarization electric field strength and electron donation capacity, ensuring uniform shape and reduced metal leaching.
The Fe-Co-N@C catalyst exhibits higher catalytic activity, achieving a 92.5% pollutant removal efficiency within 60 minutes with improved PMS adsorption and electron donation, outperforming Fe-N@C and Co-N@C catalysts, and maintaining activity across a wide pH range.
Smart Images

Figure CN119215950A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemical materials and pollutant treatment, and in particular to a method for preparing a Co-doped Fe-Co-N@C catalytic material and a method for using the same in advanced oxidation treatment of wastewater. Background Art
[0002] Advanced oxidation treatment technology is an efficient and promising wastewater treatment technology that can be used to treat a variety of polluted water bodies. Compared with traditional advanced oxidation technologies (such as Fe 2+ / H2O2, UV / H2O2), persulfate technology for degradation of refractory organic matter (AOPs) has many excellent properties and has a broad application prospect in the field of environmental remediation. Among them, heterogeneous catalysts have attracted much attention in recent years in the field of advanced oxidation degradation of organic matter due to their advantages such as high catalytic efficiency, good stability and easy recovery.
[0003] At present, many studies have shown that doping Fe-SACs into carbonitride materials can achieve good PMS activation performance, and in most studies, isolated single Fe-N4 molecules are considered to be the main active sites. However, the symmetrical Fe-N4 structure, due to its strong intermediate adsorption ability, will cause shielding of the active sites, resulting in a decrease in overall activity (Engineering Unsymmetrically Coordinated Fe Sites via HeteroatomPairs Synergetic Contribution for Efficient Oxygen Reduction. Small, 2023: 2304303.). Asymmetric coordination structures show great potential in regulating the adsorption of reaction intermediates at active sites, for example. For example, Zhang et al. found that the coordination of S in FeN4S1 and CoN3S1 leads to asymmetric coordination of the metal center, forming a polarization electric field centered on Fe, which induces a lower intermediate energy barrier and improves the catalytic activity (Uniform N-Coordinated Single-Atomic Iron Sites Dispersed in Porous Carbon Framework to Activate PMS for Efficient BPA Degradation via High-Valent Iron-Oxo Species). Therefore, it is of great practical significance to prepare a new Fe-NC catalyst with an asymmetric coordination structure to enhance its catalytic activity. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art and solve the problem that the intermediate products of the traditional Fe-N catalyst are too strongly adsorbed on the active sites due to the symmetrical coordination structure, thereby limiting the catalytic activity, the purpose of the present invention is to provide a Co-doped Fe-Co-N@C catalyst and a preparation method thereof, and to provide a method for using the catalyst material for advanced oxidation treatment of wastewater.
[0005] Therefore, the present invention successfully prepared a novel asymmetric coordinated bimetallic single atom catalyst (i.e., Fe-Co-N@C) through a three-step method of metal-organic framework material formation and post-coordination process. The post-coordination method can not only maintain the N coordination, but also adjust the asymmetric electronic structure of the Co metal atom through the post-coordinated Fe atom. x The Fe atoms in the coordination structure have a higher electron density than those in the Fe-N4 structure. The Fe-Co bimetallic co-coordination enhances the polarization electric field strength at Fe-N and Co-N, making it have stronger PMS adsorption capacity and electron donation capacity, and thus has higher catalytic activity. At the same time, compared with some existing Fe and Co metal catalysts, the catalyst of the present invention has a more uniform shape and a fuller particle size. The Fe and Co bimetallics are coordinated, and the low metal loading can effectively reduce the leaching of metal ions. At the same time, it solves the problem of few active sites and weak PMS adsorption effect in nanoparticle catalysts, and can efficiently remove organic pollutants in water.
[0006] In order to achieve the above object, the present invention adopts the following technical solution.
[0007] A method for preparing a Co-doped Fe-Co-N@C catalyst comprises the following steps:
[0008] S1. Synthesize Zn-Co-ZIF precursor. The specific steps are as follows:
[0009] (1) Dissolve zinc nitrate hexahydrate and cobalt nitrate hexahydrate in methanol and mark the solution as solution A;
[0010] (2) Dissolve 2-methylimidazole in methanol in another beaker and mark it as solution B;
[0011] (3) Stir solutions A and B separately with a glass rod. After they are completely dissolved, pour solution B into solution A and stir on a magnetic stirrer for 1 to 4 hours. After stirring, let the solution stand for 12 to 24 hours, wash with methanol, centrifuge and precipitate, then vacuum dry at 60 to 80 ° C for 12 to 24 hours to obtain a Zn-Co-ZIF precursor.
[0012] S2. Mix the Zn-Co-ZIF precursor with iron phthalocyanine to obtain Fe-Co-MOF. The specific steps are as follows:
[0013] The obtained Zn-Co-ZIF precursor was dispersed in a beaker with 20-40 mL of N,N-dimethylformamide (DMF), and then 10-30 mg of iron phthalocyanine was added to the turbid solution, ultrasonicated for 5 min to dissolve it, placed on a magnetic stirrer and heated and stirred at 60-80 ° C for 1-4 h, and finally the precipitate was collected by centrifugation and vacuum dried at 80 ° C to obtain Fe-Co-MOF.
[0014] S3, Zn in Fe-Co-MOF was pyrolyzed 2+ Evaporation, in the cavity of the ZIF framework, Fe atoms and Co atoms will form coordination with N atoms together to obtain Fe-Co-N@C catalyst. The specific operation is:
[0015] The obtained Fe-Co-MOF was placed in a quartz boat, which was then placed in a tube furnace. Nitrogen was then introduced into the tube furnace. Under this condition, the temperature was increased to 700-900°C at a heating rate of 2-10°C / min and maintained for 2-4 hours. After the tube furnace was cooled down, the sample was taken out, washed with methanol, and dried in a vacuum drying oven at 60-80°C for 12-24 hours to obtain a Fe-Co-N@C catalyst.
[0016] Preferably, in step S1 (1), the molar ratio of zinc nitrate hexahydrate to cobalt nitrate hexahydrate is 20 to 50:1, preferably 35:1.
[0017] Preferably, in step S1 (1), the molar ratio of zinc nitrate hexahydrate to methanol is 1:70-150, preferably 1:120; the molar ratio of cobalt nitrate hexahydrate to methanol is 1:3000-4500, preferably 1:3500.
[0018] Preferably, in step S1 (2), the molar ratio of 2-methylimidazole to methanol is 1:10 to 50, preferably 1:35.
[0019] More preferably, in step S1 (3), the stirring time is 2 hours.
[0020] More preferably, in step S1 (3), the static aging time is 12 hours.
[0021] More preferably, in step S1 (3), the vacuum drying temperature is 60° C. and the vacuum drying time is 12 h.
[0022] More preferably, in step S2, the mass ratio of Zn-Co-ZIF to iron phthalocyanine is 15 to 50:1, preferably 35:1.
[0023] In step S2, the organic solvent is a solvent that can interact with the π electron system on the phthalocyanine ring, such as N,N-dimethylformamide (DMF).
[0024] Preferably, in step S3, the heating rate is 5°C; the calcination temperature is 800°C, and the calcination time is 3h.
[0025] Further preferably, in step S3, the temperature of the tube furnace is lowered to room temperature at a rate of 5°C / min.
[0026] Further preferably, in step S3, the vacuum drying temperature is 60° C., and the vacuum drying time is 12 h.
[0027] The present invention provides a Co-doped Fe-Co-N@C catalyst prepared by the synthesis method, which uses a porous carbon material as a carrier, and the surface and interior of the carrier are a coordination structure of iron, cobalt metal atoms and nitrogen atoms. The porous carbon material structure is a prismatic dodecahedron, and the carrier has a microporous structure with a pore size of 1-2 nm.
[0028] The present invention also provides a method for applying the Co-doped Fe-Co-N@C catalyst to advanced oxidation treatment of wastewater, wherein Fe-Co-N@C catalyst powder is added to a solution containing a certain concentration of target organic pollutants, and then a certain amount of oxidant is immediately added to react.
[0029] Further preferably, the dosage of the Fe-Co-N@C catalyst is 0.1-1 g / L.
[0030] More preferably, the concentration of the organic pollutants is 5 to 20 mg / L.
[0031] Further preferably, the oxidant is at least one of potassium persulfate, sodium persulfate, sodium persulfate and potassium persulfate.
[0032] Further preferably, the mass ratio of the Fe-Co-N@C catalyst to the oxidant is 1:3-12.
[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0034] (1) When introducing Fe, the present invention uses N,N-dimethylformamide (DMF), a solvent that can interact with the π electron system on the phthalocyanine ring, to generate a dipole-induced dipole interaction with the π electron system, thereby enhancing the molecular binding between single-molecule iron phthalocyanine and Zn-Co-ZIF, and obtaining Fe / Co single-atom dispersed Fe-Co-ZIF, thereby solving the problem in the prior art that iron phthalocyanine is insoluble, uneven doping leads to the production of iron clusters, and an effective single-atom Fe / Co coordinated coordination structure cannot be formed. In the prior art, methanol is usually used as an organic solvent to mix Fe and Zn-Co-ZIF. Solvents such as methanol will not interact with iron phthalocyanine, and iron phthalocyanine will not dissolve, so it will cause Fe to easily agglomerate on Zn-Co-ZIF, and an effective single-atom Fe / Co coordinated coordination structure cannot be generated.
[0035] (2) The present invention prepares Fe-Co-N@C catalyst by pyrolysis of Fe and Co co-doped ZIF nanomaterials. When the obtained Fe-Co-N@C is used to activate PMS to degrade organic pollutants, it is found that Fe-Co-N x Coordination structure ratio FeN x and CoN x It exhibits better catalytic performance. Thanks to the synergistic effect of single-atom Fe and Co in asymmetric coordination configuration, the prepared Fe-Co-N@C exhibits a maximum pollutant removal efficiency of 92.5% within 60 minutes, and the calculated reaction rates are 1.41 and 2.93 times that of Fe-N@C catalyst and Co-N@C catalyst, respectively. In addition, Fe-Co-N@C exhibits good catalytic activity in a wide pH range of pH = 2.0 to 10.0, and has good application prospects in actual wastewater treatment.
[0036] (3) The Fe-Co-N@C catalyst preparation method proposed in the present invention has simple equipment, mild reaction conditions, easy process control, metal distribution in single atomic form, extremely high atomic utilization, no need to add toxic and harmful reagents, and is convenient for the industrialization and engineering application of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Scanning electron microscopy, transmission electron microscopy, HAADF and MAPPING images of Fe-Co-N@C synthesized in Example 1 of the present invention, Fe-N@C in Comparative Example 1, and Co-N@C in Comparative Example 2.
[0038] Figure 2 This is the X-ray photoelectron spectrum of Fe-Co-N@C synthesized in Example 1 of the present invention.
[0039] Figure 3The degradation effects of Fe-Co-N@C of Example 1 of the present invention, Fe-N@C of Comparative Example 1 and Co-N@C of Comparative Example 2 are compared.
[0040] Figure 4 The figure is a comparison of the degradation effects of the Fe-Co-N@C catalyst of the present invention under different catalyst dosage conditions.
[0041] Figure 5 The figure is a comparison of the degradation effects of the Fe-Co-N@C catalyst of the present invention under different oxidant dosage conditions.
[0042] Figure 6 The degradation effects of the Fe-Co-N@C catalyst synthesized in the present invention are compared under different initial pH conditions.
[0043] Figure 7 This is to evaluate the recycling performance of the Fe-N / O@C catalyst synthesized in the present invention.
[0044] Figure 8 This is a comparison chart of the XPS spectra of C1s and N1s of the Fe-N / O@C catalyst synthesized by the present invention before and after the reaction.
[0045] Table 1 compares the N1s XPS fitting results of Fe-Co-N@C synthesized in Example 1 of the present invention, Fe-N@C in Comparative Example 1, and Co-N@C in Comparative Example 2.
[0046] Table 2 is a comparison of the XPS fitting results of C1s and N1s of Fe-Co-N@C synthesized in Example 1 of the present invention before and after the reaction. DETAILED DESCRIPTION
[0047] The specific embodiments of the present invention are further described below. It should be noted that the description of the embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0048] Example 1
[0049] Preparation of solution A: Add 3.57g of Zn(NO3)2·6H2O and 0.1g of Co(NO3)2·6H2O to 60mL of methanol solution and ultrasonicate until dissolved. Preparation of solution B: Add 3.84g of 2-methylimidazole to 60mL of methanol and ultrasonicate until dissolved. Then mix the two solutions, stir at room temperature for 2h, and then let it settle for 12h. Finally, collect the precipitate by centrifugation and dry it in a vacuum oven at 60℃ for 12h to obtain Zn-Co-ZIF. Take 0.5g of Zn-Co-ZIF and disperse it in 30mL of N,N-dimethylformamide (DMF), then add 15mg of iron phthalocyanine to the turbid solution, ultrasonicate for 5min, then heat and stir at 80℃ for 2h, and finally collect the precipitate by centrifugation and vacuum dry it at 80℃ to obtain Fe-Co-MOF. The dried Fe-Co-MOF was placed in a quartz boat and calcined in a tube furnace at 800°C for 3 h at a heating rate of 5°C / min under a nitrogen atmosphere. The calcined product was ground to obtain Fe-Co-N@C.
[0050] Comparative Example 1
[0051] Preparation of solution A: Add 3.57g of Zn(NO3)2·6H2O to 60mL of methanol solution and ultrasonicate until dissolved. Preparation of solution B: Add 3.84g of 2-methylimidazole to 60mL of methanol and ultrasonicate until dissolved. Then mix the two solutions, stir at room temperature for 2h, then let it settle for 12h, finally collect the precipitate by centrifugation, and dry it in a vacuum oven at 60℃ for 12h to obtain Zn-ZIF. Take 0.5g of Zn-Co-ZIF and disperse it in 30mL of N,N-dimethylformamide (DMF), then add 0.115g of iron phthalocyanine to the turbid solution, ultrasonicate for 5min, then heat and stir at 80℃ for 2h, finally collect the precipitate by centrifugation and vacuum dry it at 80℃ to obtain Fe-Zn-MOF. The dried Fe-Zn-MOF was placed in a quartz boat and calcined in a tube furnace at 800°C for 3 h at a heating rate of 5°C / min under a nitrogen atmosphere. The calcined product was ground to obtain Fe-N@C.
[0052] Comparative Example 2
[0053] Preparation of solution A: Add 3.57g of Zn(NO3)2·6H2O and 0.115g of Co(NO3)2·6H2O to 60mL of methanol solution and ultrasonicate until dissolved. Preparation of solution B: Add 3.84g of 2-methylimidazole to 60mL of methanol and ultrasonicate until dissolved. Then mix the two solutions, stir at room temperature for 2h, then let it settle for 12h, finally collect the precipitate by centrifugation, and dry it in a vacuum oven at 60℃ for 12h to obtain Zn-Co-ZIF. Take 0.5g of Zn-Co-ZIF and disperse it in 30mL of N,N-dimethylformamide (DMF), ultrasonicate for 5min, then heat and stir at 80℃ for 2h, finally collect the precipitate by centrifugation and vacuum dry it at 80℃ to obtain Zn-Co-MOF. The dried Zn-Co-MOF was placed in a quartz boat and calcined in a tube furnace at 800°C for 3 h at a heating rate of 5°C / min under a nitrogen atmosphere. The calcined product was ground to obtain Co-N@C.
[0054] The SEM and TEM images of the prepared catalysts are shown in Figure 2. Figure 1 As shown in Figure 2, Fe-N@C and Co-N@C maintain a complete regular dodecahedral rhombus structure ( Figure 1 (b1) and (c1)), the surface is smooth and the crystals are full. In contrast, the surface of Fe-Co-N@C becomes rough ( Figure 1 (a1)), and wrinkles appear at the edge of the crystal, and carbon nanotubes are produced. In addition, Fe-Co-N@C shows the most serious surface collapse and the thinnest carbon wall, which is because phthalocyanine iron decomposes into free Fe atoms when calcined at 800℃. These free Fe atoms will occupy the defect sites formed by the pyrolysis of Zn at high temperature together with Co, and form coordination with N together. HAADF-STEM images show that ( Figure 1 (a2), (b2) and (c2)), no metal nanoparticles or metal oxide nanoparticles can be observed in Fe-N@C, Co-N@C and Fe-Co-N@C. At the same time, the energy dispersive X-ray (MAPPING) spectrum ( Figure 1 (a4), (b4) and (c4)) also show that Fe, Co, C and N species are uniformly distributed in the carbon matrix, which confirms that Fe and Co exist in an atomically dispersed state.
[0055] By X-ray photoelectron spectroscopy (XPS, Figure 2 ) The internal structures of the Fe-Co-N@C, Fe-N@C and Co-N@C catalysts synthesized in Example 1 were further analyzed. The C1s fine spectra of the three materials ( Figure 2 There are four types of characteristic peaks in (a) and (b), corresponding to CC sp 2(284.7eV), CO / CN (285.8eV), C=O (288.3eV) and π-π* (291.0eV). The fine spectrum of N 1s ( Figure 2 (b)) can be divided into four characteristic peaks, of which 398.3eV is the characteristic peak belonging to pyridinic N / MN (M is Fe and Co). Compared with Fe-N@C and Co-N@C, Fe-Co-N@C has a slight shift and is located between the two, which indicates that pyridinic N is combined with Fe and Co atoms in the form of coordination bonds. The characteristic peaks at 399.4eV, 400.8eV and 402.5eV belong to pyrrolic N, graphitic N and oxidized N, respectively. Table 1 compares the relative contents of various N species in the three catalytic materials. The contents of pyrrolic N and graphitic N in Fe-Co-N@C are higher, which is beneficial to improve the adsorption performance of pollutants. Figure 2 (c) Comparison of the Fe 2p spectra of Fe-Co-N@C and Fe-N@C. The peaks near 712.5 eV and 723.6 eV correspond to the Fe 2p 3 / 2 and Fe 2p 1 / 2 , it can be seen that the Fe peak of Fe-Co-N@C has an obvious negative shift. Figure 2 (d) Comparison of the Co2p spectra of Fe-Co-N@C and Co-N@C. 779.7 eV and 797.0 eV belong to Co 2p, respectively. 3 / 2 and Co 2p 1 / 2 , the Co peak of Fe-Co-N@C also has a negative shift. The change in XPS binding energy often represents a change in electron density, and a decrease in binding energy means an increase in singleton density. Therefore, the coordination form of the two metal atoms may increase the polarization electric field intensity of the charge-rich centers of both, thereby showing better catalytic performance.
[0056] Table 1 N1s fitting results of Fe-Co-N@C, Co-N@C and Fe-N@C
[0057]
[0058] Example 2
[0059] In this example, Fe-Co-N@C of Example 1, Fe-N@C of Comparative Example 1 and Co-N@C of Comparative Example 2 were used to degrade target organic pollutants (bisphenol AF, BPAF) to evaluate their catalytic performance. The specific operation is as follows: Fe-Co-N@C of Example 1, Fe-N@C of Comparative Example 1 and Co-N@C of Comparative Example 2 were added to a solution containing 10 mg / L of target organic pollutants, and 0.6 g / L of PMS was added for reaction.
[0060] like Figure 3As shown in (a), it can be seen that the removal rate of BPAF by adsorption alone is limited, and the adsorption removal rate after 60 minutes is only 4.5-6.7%. The removal rate of BPAF by PMS alone within 60 minutes is 3.2%, which shows that in the absence of a catalyst, PMS can hardly degrade by self-decomposition to produce ROS. When the catalyst and PMS are added at the same time, the removal rate of BPAF is greatly improved. The removal rates of BPAF in the three catalyst systems after 60 minutes of reaction are 56.5%, 79.2% and 88.3%, respectively. Fe-Co-N@C shows the best catalytic performance. By comparing the pseudo-first-order kinetic constants ( Figure 3 (b) It can be seen that the k of the Fe-Co-N@C / PMS system is 2.93 times and 1.41 times that of Co-N@C / PMS and Fe-N@C / PMS, respectively. This is due to the bimetallic coordination of Fe-Co-N x The change in the site electron configuration breaks the inertness brought by the symmetrical structure of Fe-N4 and Co-N4.
[0061] Example 3
[0062] In order to further evaluate the effect of catalyst dosage on the degradation of BPAF in the Fe-Co-N@C / PMS system. According to the preparation method of Example 1, the synthesized Fe-Co-N@C catalyst was added to 100 mL of BPAF solution and reacted in a 250 mL blue-capped bottle. The control conditions for the reaction were a pollutant concentration of 10 mg / L and a permonosulfate (PMS) concentration of 0.6 g / L. The catalyst dosage range was 0.1 to 0.4 g / L. Figure 4 As shown in the figure, when the catalyst concentration increased from 0.1g / L to 0.2g / L, the BPAF removal rate increased from 43.9% to 89.8%. When the catalyst concentration was further increased to 0.4g / L, the removal rate reached 94.6%, and BPAF could be completely removed. The improvement in the reaction rate was not very obvious. This is because the more catalysts there are, the more active sites there are, and the higher the activation efficiency of PMS, which produces more reactive oxygen species (ROS) to degrade BPAF. However, when the active sites are in excess, not all sites can fully contact PMS due to the concentration of PMS, which results in the reaction rate being unable to be further improved.
[0063] Example 4
[0064] In order to further evaluate the effect of catalyst dosage on the degradation of BPAF by the Fe-Co-N@C / PMS system. According to the preparation method of Example 1, the synthesized Fe-Co-N@C catalyst was added to 100 mL of BPAF solution and reacted in a 250 mL blue-capped bottle. The control conditions for the operation of the reaction were a pollutant concentration of 10 mg / L and a catalyst dosage of 0.3 g / L. The PMS concentration range was 0.3 to 1.2 g / L. Figure 5 As shown in the figure, as the PMS dosage increased from 0.3g / L to 0.9g / L, the BPAF removal rate also increased from 75.7% to 92.5%. This is because the increase in PMS dosage promoted the production of more ROS, thereby increasing the degradation rate of BPAF. When the PMS dosage was further increased to 1.2g / L, the reaction rate of the system only increased slightly, while the BPAF removal rate dropped to 91.8%. This is because the excessive addition of PMS will produce a large number of free radicals in a short period of time, which will cause the self-quenching of free radicals and lead to a decrease in the final removal rate.
[0065] Example 5
[0066] In order to further analyze the effect of Fe-N / O@C material on the activation performance of PMS under different initial pH conditions. The Fe-Co-N@C catalyst prepared in Example 1 was added to the BPAF solution with initial pH = 2.0, 6.0, 8.0, and 10.0, respectively, and reacted in a 250mL blue-capped bottle. The control conditions for the operation of the reaction were catalyst dosage of 0.1g / L, pollutant concentration of 10mg / L, and permonosulfate (PMS) concentration of 0.6g / L. Figure 6 As shown in the figure, in the acidic range of initial pH = 2 to 6, the removal rate of BPAF by the Fe-Co-N@C / PMS system is 91.3-92.9%, and the best removal rate is achieved at pH = 4. When no additional acid or alkali is added, the initial pH of the solution is about 8, at which the removal rate of BPAF is 89.8%. When the initial pH is further increased to a strong alkaline state, the removal rate decreases slightly, but is still 86.2%, which may be due to the fact that HSO5 - Under alkaline conditions, it is easily dissociated into SO5 2- , and its oxidation ability is relatively weak. But overall, the Fe-Co-N@C / PMS system can maintain a high BPAF removal rate in a relatively wide pH range, which is sufficient to prove that Fe-Co-N@C has potential in practical applications.
[0067] Example 6
[0068] In order to further investigate the cyclic stability of Fe-Co-N@C materials, the Fe-Co-N@C catalyst prepared in Example 1 was subjected to a cyclic experiment for removing organic pollutants. Figure 7 As shown in the figure, after each reaction, the catalyst can be reused by simple solid-liquid separation and drying without any other treatment. Fe-Co-N@C can still maintain an 80% removal rate after 3 cycles, indicating that the prepared catalyst has good cyclic stability.
[0069] Example 7
[0070] We performed XPS characterization on the catalyst materials before and after the reaction to analyze the catalytic mechanism in the system. Figure 8 As shown in Table 2, overall, the types of characteristic peaks in the C1s and N1s fine spectra of Fe-Co-N@C before and after the reaction did not change, but their corresponding binding energies changed. Figure 8 (a) It can be found that after the reaction, the binding energies of CO / CN (286.2eV) and C=O (288.4eV) increased by 0.4eV and 0.1eV respectively. The increase in binding energy means that these sites act as electron donors, while the binding energy of the π-π* site changes greatly (1.5eV). This is because this site is likely to bind to BPAF and its byproducts (mainly byproducts containing benzene rings), resulting in electronic interactions, which leads to an increase in binding energy. Comparing the fine spectrum of N1s ( Figure 8 (b) We can find that the binding energy of the characteristic peak corresponding to pyridine N / MN (398.2 eV) increased by 0.1 eV, while the binding energies corresponding to the characteristic peaks of pyrrole N (399.1 eV) and graphite N (400.4 eV) decreased by 0.3 eV and 0.4 eV, respectively, indicating that the pyridine N / MN site acts as an electron donor, while pyrrole N and graphite N participate in the reaction as electron acceptors.
[0071] Table 2 Fitting results of C1s and N1s before and after the reaction of Fe-Co-N@C
[0072]
[0073] Finally, it should be noted that the above embodiments are only preferred implementations of the present invention and are only used to explain the present invention, not to limit the present invention. For those skilled in the art, they can still modify the technical solutions recorded in the above embodiments, or replace some of the technical features therein with equivalents. Any changes, replacements and modifications made within the spirit and principles of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a Co-doped Fe-Co-N@C catalyst for advanced oxidation treatment of wastewater, characterized in that: The following steps are involved: S1. Preparation of solution A: adding zinc nitrate hexahydrate and cobalt nitrate hexahydrate to a methanol solution and sonicating until dissolved; preparation of solution B: adding 2-methylimidazole to an alcohol and sonicating until dissolved, then mixing the two solutions, stirring at room temperature, and then standing to precipitate, finally collecting the precipitate by centrifugation, and drying it in a drying oven under vacuum to obtain Zn-Co-ZIF; S2, dispersing Zn-Co-ZIF in N,N-dimethylformamide DMF, then adding iron phthalocyanine to the turbid solution, dissolving it by ultrasonication, then stirring under heating conditions, and finally collecting the precipitate by centrifugation and drying it in a vacuum drying oven to obtain Fe-Co-MOF; S3. The obtained Fe-Co-MOF precursor is placed in a quartz boat, and then the quartz boat is placed in a tube furnace. Subsequently, nitrogen is introduced into the tube furnace, and the temperature is increased for calcination. The obtained calcined product is cooled and ground to obtain Fe-Co-N@C.
2. The method for preparing the Co-doped Fe-Co-N@C catalyst for advanced oxidation treatment of wastewater according to claim 1, characterized in that: In step S1, the molar ratio of zinc nitrate hexahydrate to methanol is 1:70-150; the molar ratio of cobalt nitrate hexahydrate to methanol is 1:3000-4500; and the molar ratio of 2-methylimidazole to methanol is 1:10-50.
3. The method for preparing the Co-doped Fe-Co-N@C catalyst for advanced oxidation treatment of wastewater according to claim 1, characterized in that: In step S1, the stirring time is 1 to 4 hours; the static sedimentation time is 12 to 24 hours.
4. The method for preparing the Co-doped Fe-Co-N@C catalyst for advanced oxidation treatment of wastewater according to claim 1, characterized in that: In step S1, the vacuum drying temperature is 60-80°C, and the vacuum drying time is 12-24 hours.
5. The method for preparing the Co-doped Fe-Co-N@C catalyst for advanced oxidation treatment of wastewater according to claim 1, characterized in that: In step S2, the mass ratio of the iron phthalocyanine to the Zn-Co-ZIF is 1:15 to 1:50; the amount of N,N-dimethylformamide DMF added is 20 to 40 mL, and the temperature limit for stirring and heating is 60 to 80°C.
6. The method for preparing the Co-doped Fe-Co-N@C catalyst for advanced oxidation treatment of wastewater according to claim 1, characterized in that: In step S3, the heating rate is 2-10°C / min; the calcination temperature is 700-900°C, and the calcination time is 2-4h.
7. The method for preparing the Co-doped Fe-Co-N@C catalyst for advanced oxidation treatment of wastewater according to claim 1, characterized in that: In step S3, the temperature of the tube furnace is lowered to room temperature at a rate of 2 to 10°C / min; the vacuum drying temperature is 60 to 80°C, and the vacuum drying time is 12 to 24 hours.
8. A Co-doped Fe-Co-N@C catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: A porous carbon material is used as a carrier, and the surface and interior of the carrier are coordination structures of iron, cobalt metal atoms and nitrogen atoms. The porous carbon material structure is a prismatic dodecahedron, and the metal is distributed in the form of single atoms.
9. Use of a Co-doped Fe-Co-N@C catalyst as claimed in claim 8 in removing organic pollutants from water by advanced oxidation technology, characterized in that: Co-doped Fe-Co-N@C catalyst powder was added to a solution containing the target organic pollutants, followed by the immediate addition of an oxidant for the reaction.
10. The use according to claim 9, characterized in that: The dosage of the Fe-Co-N@C catalyst is 0.1-1 g / L; the concentration of the organic pollutants is 5-20 mg / L; the oxidant is at least one of potassium persulfate, sodium persulfate, sodium persulfate and potassium persulfate; the mass ratio of the Fe-Co-N@C catalyst to the oxidant is 1:2-10.
Citation Information
Patent Citations
Carbon nanocage loaded iron-based metal para-site catalyst as well as preparation method and application thereof
CN116826082A
Preparation method and application of Fe-Ni / CN bimetallic monatomic catalyst with nitrogen-doped carbon as substrate
CN117920299A
Gamma-Fe composite Fe-N / O-C catalyst for advanced oxidation treatment of wastewater and preparation method of gamma-Fe composite Fe-N / O-C catalyst
CN118122360A